A CULTURE OF KINSHIP: CHINESE GENEALOGIES AS A SOURCE FOR RESEARCH IN DEMOGRAPHIC ECONOMICS. (14th November 2016) - Shiue, Carol H.
Abstract: This paper discusses the use of Chinese genealogies for research on economic demography. I focus both on what is known about the genealogy as a data source, and what are the open questions for future research. Chinese genealogies contain records at the individual level. With the publication of new catalogs and efforts to collect genealogies, the number of genealogies is even larger than previously thought, with most dating to the late Ming (1368–1644) and Qing (1644–1911) Dynasties. These records contain a rich source of information about the Chinese population history, over a period for which there is no alternative source of information. Yet, the source still remains largely unexploited. Although the work of transcribing the data is significant, and selection biases need to be carefully considered, preliminary analysis of the data for a sample of married men for Tongcheng County in Anhui Province suggests these data are a rich source of information for demographic and economics research.